DigComp Gestão Escolar: concepção de um instrumento de autoavaliação das competências digitais para gestores escolares - Brito, Mateus de Lima (2023)
Digital Information and Communication Technologies (TDICs) are inserted in Teaching Institutions as a set of opportunities that mediate, facilitate and develop pedagogical and administrative processes at different levels of educational performance. Therefore, it is necessary to ensure, in addition to access to TDICs, actions that develop the Digital Competences (DCs) of the subjects involved in the teaching and learning processes. However, in the context of basic education, offering continuing education only to teachers is not enough to guarantee the good performance of students, since the responsibility for the results also belongs to School Managers. Therefore, the objective of this study is to identify the DCs of School Managers through a Self-Assessment Instrument. For that, the study had as methodological procedures, the bibliographical and documental research that provided the theoretical foundation, as well as a basic research with a qualitative approach and for the reach of the objectives it was applied the exploratory, descriptive research and a case study with 420 Managers Students that occurred during an extension course of the Digital Educational Laboratory of UFC Virtual. For data collection, a questionnaire was initially applied to map the personal and professional profile of School Managers and another that sought to identify what type of technologies were used in school management. Based on the questionnaires above and on the European Framework of Digital Competences for Educators, a self-assessment instrument was constructed divided into administrative, financial, pedagogical and human resources areas, with five CDs in each area and five levels of proficiency classified as Apprentice, Researcher, Integrator, Specialist and Leader. After its application, it was possible to identify, through the results, that the level of DCs of the participants in this sample were at the Integrator Level, which is defined as the existence of the use of TDICs in professional practice, but they are still trying to understand which tools technologies can improve school management processes. There was also a lack of theoretical references in the Brazilian literature on DCs for school managers. There was a lack of continuing education in the area of educational technologies, thus confirming the relevance of this study, which could serve as a basis for further research with a similar theme. In view of the results, it was possible to develop the Educational Product of this Dissertation, called DigComp Gestão Escolar, which is a CD Self- Assessment Instrument for School Managers and which is available in a digital repository on the web, with public and free access. As future works, it is proposed a continuity of the research through strategies that develop the DCs of School Managers such as: an orientation guide on DCs, continuous or in-service training in this area and partnership between university and school in the promotion of DCs in the field of school management.